Painting with words, writing with pictures : word and image in the work of Italo Calvino - Ricci, Franco, 1953- (University of Toronto Press, 2001)
Ricci's book ranges widely over Calvino's oeuvre to illustrate the accuracy of the idea articulated by Calvino himself that a visual image lies at the origin of all his narrative.
Keywords: Calvino, Italo -- Criticism and interpretation.; Calvino, Italo -- Critique et interprétation.; Calvino, Italo; Calvino, Italo -- Ästhetik und Poetik.; Calvino, Italo -- Werk.; Calvino, Italo, -- 1923-1985 -- analys och tolkning.; LITERARY CRITICISM -- European -- Italian.; Electronic books.; e-books.; Criticism, interpretation, etc.; Livres numériques.